C. elegans La-related protein, LARP-1, localizes to germline P bodies and attenuates Ras-MAPK signaling during oogenesis - Nykamp, Keith (Cold Spring Harbor Laboratory Press, 2008)
RNA regulators are critical for animal development, especially in the germ line where gene expression is often modulated by changes in mRNA stability, translation, and localization. In this paper, we focus on Caenorhabditis elegans LARP-1, a representative of one La-related protein (Larp) family found broadly among eukaryotes. LARP-1 possesses a signature La motif, which is an ancient RNA-binding domain, plus a second conserved motif, typical of LARP-1 homologs and therefore dubbed the LARP1 domain. LARP-1 appears to bind RNA in vitro via both the La motif and the LARP1 domain. larp-1 null mutants have an oogenesis defect reminiscent of hyperactive Ras-MAPK signaling; this defect is suppressed or enhanced by down- or up-regulating the Ras-MAPK pathway, respectively. Consistent with a role in down-regulating the Ras-MAPK pathway, larp-1 null mutants have higher than normal levels of selected pathway mRNAs and proteins. LARP-1 protein colocalizes with P bodies, which function in RNA degradation. We suggest that LARP-1 functions in P bodies to attenuate the abundance of conserved Ras-MAPK mRNAs. We also propose that the cluster of LARP-1 homologs may function generally to control the expression of key developmental regulators.